Correlation Between Management of Teaching Learning Resources and Pupils Performance at the Basic Level in Tutuka Circuit Schools of Obuasi, in the Ashanti Region of Ghana - Kor, Jacob Aaworb-nang Maabobr; Kyeremeh, Alex (Advances in Social Sciences Research Journal, 2022)
The purpose of this study was to find out whether there was any significant correlation between management of Teaching/Learning Resources (TLRs) available in schools within Tutuka circuit and students’ performance at the BECE examinations. A correlational design was used for the study. The sample for the study consisted of head teachers and teachers. The total target population was 127 from which a sample of 125 was purposively selected. Ten head teachers and 115 teachers participated in the study. Data for the study were collected using two sets of questionnaire, one for head teachers and another for teachers. The study revealed that there was an inverse correlation (R = - 0.461) between management of TLRs and students’ performance as measured by the BECE results. This value was not statistically significant. The study also showed that TLRS were released to schools in Tutuka Circuit on time and were efficiently managed by head teachers. The study therefore recommends that management of TLRs be made an essential part of in-service training for all head teachers to ensure that students derive maximum benefit from the available resources.